Regions as Hubs of Knowledge : Conditions and Determinants of Development - Golejewska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Innovations, associated with accumulation of knowledge, research and development and productivity growth, determine first of all competitiveness of the best developed regional economies, defined as hubs of knowledge. The aim of the article is an analysis of this type of regions and a survey of fundamental theoretical concepts of its competitiveness. An important role in creation and circulation of knowledge is assigned to networks. Results of empirical analysis confirm their diversity depending on assumptions, measures and size of the analysed group. Competitiveness is not a static concept. Regions once assigned to the group of knowledge hubs, do not have to stay there permanently. It depends, in large measure, on their development strategies and effectiveness of regional policy.